Towards optimal regimens of parenteral quinine for young African children with cerebral malaria: unbound quinine concentrations following a simple loading dose regimen. - Winstanley, P; Mberu, E; Watkins, WM; Murphy, SA; Lowe, B; Marsh, K (1994)
Nine children with severe falciparum malaria were treated with an intravenous quinine regimen which did not require burettes or infusion pumps, to determine its practicability and to ensure that therapeutic drug concentrations were achieved and maintained throughout the dose interval. The regimen comprised quinine dihydrochloride (15 mg/kg; 12.5 mg/kg of the free base), which was added to a bag of intravenous fluid (after wastage of all but 100 mL), and given via standard giving sets over 2 h. Blood was drawn sequentially during the infusion, and for 12 h thereafter; plasma water was obtained by ultrafiltration of samples at the bedside, and quinine concentration was measured, in plasma and plasma water, by high performance liquid chromatography. Drug administration was practicable without burettes or infusion pumps; unbound drug concentrations exceeded the 99% inhibitory concentration for local parasites within 0.5 h, and remained within the therapeutic range for the entire dose interval. This loading dose regimen can now be recommended for young children in African hospitals; maintenance doses of 10 mg/kg should be given at 12 h intervals until oral antimalarial drugs are possible. These recommendations will need to be modified if susceptibility to quinine declines.